Utility of Bispectral Index Monitor as a Tool to Detect and Manage Intraoperative Seizure: A Case Series - Dey, Sandeep; Tyagi, Megha; Goyal, Amit; Kumar, Pallav (Journal of Neuroanaesthesiology and Critical Care, 2025)
Conventional electroencephalogram (EEG) has been the most common method to detect and manage seizure episodes. Limitations to its use in the intraoperative period during neurosurgical cases have made detecting intraoperative seizure almost impractical, especially in the presence of a neuromuscular blocking agent. Using an EEG-based monitor like bispectral index (BIS) can add a new dimension to intraoperative neuromonitoring in patients at risk of seizure. Apart from other indices, it also displays the real-time raw EEG waveform, which can be valuable in diagnosing an intraoperative seizure and guide the therapeutic achievement of burst suppression. An increase in the BIS value has also been reported during intraoperative seizures. Here, we present the cases of three patients posted for excision of intracranial space-occupying lesions who developed intraoperative seizures, which were diagnosed and managed with the aid of a BIS monitor. This case series highlights the utility of BIS in detecting and managing intraoperative seizures, apart from its role in depth of anesthesia monitoring.
Keywords: bispectral index; burst suppression; depth of anesthesia; electroencephalogram; Intraoperative seizure